An ultrasonographic study to evaluate the correlation of calcified yolk sac with spontaneous abortion - Srivastava, Geetanjali; Mumal Nagwani,; Tewari, Vineeta; Khanduri, Sachin; Kunwar, Shipra; Prince Kapoor, (Asian Journal of Medical Sciences, 2022)
Background: The yolk sac is a small, membranous structure, which is situated outside the embryo and has a variety of functions during embryonic development. The yolk sac plays an important role in critical biological functions during early gestation, which includes primitive hematopoiesis as well as production of germ cells. It can be visualized between 6 and 12 weeks of pregnancy by ultrasonography as a regularly rounded extra-amniotic structure when the gestational sac reaches dimensions of 8–10 mm. On sonography, the yolk sac appears as a round structure which has an anechoic center bordered by a regular well-defined echogenic rim. Thus, a normal yolk sac is a yolk sac with echogenic rim and hypoechoic center, whereas yolk sac with hypoechoic rim or hyperechoic center is considered as calcified yolk sac. Aim and Objectives: To study the correlation of calcified yolk sac with spontaneous abortion in the first trimester of pregnancy. Materials and Methods: We studied 144 pregnant females who were in their first trimester of pregnancy, referred by the department of obstetrics and gynecology. The echotexture of yolk sac was observed by transvaginal sonography and its correlation with spontaneous abortion. Results: Yolk sac was present in 140 cases (97.22%), and in 4 cases (2.78%), it was absent. Out of 140 cases, it was calcified in two cases and normal in 138. All the cases in which there was absence of yolk sac or calcified yolk sac resulted into spontaneous abortion. Conclusion: Accurate recognition of the normal and abnormal sonographic findings related to yolk sac can be used to anticipate the course of pregnancy which may be used as good tool in clinical practice to predict whether a pregnancy is going to have a good or a poor outcome.